2022
DOI: 10.1002/clt2.12118
|View full text |Cite
|
Sign up to set email alerts
|

Preference for sublingual immunotherapy with tablets in a Spanish population with allergic rhinitis

Abstract: Background This study investigated patients' preference for allergy immunotherapy (AIT) administered as either sublingual immunotherapy‐tablets versus monthly or weekly subcutaneous immunotherapy (SCIT) from a Spanish patient perspective. Methods A discrete choice experiment (DCE) consisting of two blocks with eight choice sets in each was constructed to elicit the preferences for AIT. Three attributes were included in the DCE for the mode of administration, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…49 Studies have also demonstrated a significant preference for SLIT tablets versus SCIT among caregivers of children with allergic rhinitis. 15,16 These findings are supported by a recent systematic review and meta-analysis of SLIT drops and tablets versus SCIT in children with allergic rhinitis. 50 Whilst acknowledging the limited availability of head-to-head studies of SLIT and SCIT and the heterogeneous evidence base, the analysis suggested that SLIT may be superior to SCIT in terms of treatment-related adverse events, potentially making it a more favourable choice in paediatric populations.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…49 Studies have also demonstrated a significant preference for SLIT tablets versus SCIT among caregivers of children with allergic rhinitis. 15,16 These findings are supported by a recent systematic review and meta-analysis of SLIT drops and tablets versus SCIT in children with allergic rhinitis. 50 Whilst acknowledging the limited availability of head-to-head studies of SLIT and SCIT and the heterogeneous evidence base, the analysis suggested that SLIT may be superior to SCIT in terms of treatment-related adverse events, potentially making it a more favourable choice in paediatric populations.…”
Section: Discussionmentioning
confidence: 65%
“…2 Consequently, patient preference regarding the administration form of AIT (SCIT or SLIT) should be considered to ensure optimal adherence during the three-year treatment period. 2,15,16 SLIT can be administered in the form of drops or tablets. 2 Robust clinical evidence for SCIT and SLIT drops in paediatric populations is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, reports from the literature suggest that the majority of patients prefer SLIT (tablets) over SCIT and, that taking these preferences into account when deciding the course of treatment, could improve adherence. 35,36 However, with SLIT treatment, current adherence and persistence monitoring methods do not provide a guarantee that patients have taken their treatment or that it has been administered correctly. By contrast, all SCIT injections are delivered in the clinic and documented in the patient medical records meaning that adherence and persistence are transparent.…”
Section: G Ener Al Con S Ider Ati On S For the Apait Checklis Tmentioning
confidence: 99%
“…In contrast, the convenience of at‐home treatment provided by SLIT tablets would support better adherence and persistence. Indeed, reports from the literature suggest that the majority of patients prefer SLIT (tablets) over SCIT and, that taking these preferences into account when deciding the course of treatment, could improve adherence 35,36 . However, with SLIT treatment, current adherence and persistence monitoring methods do not provide a guarantee that patients have taken their treatment or that it has been administered correctly.…”
Section: General Considerations For the Apait Checklistmentioning
confidence: 99%